Like Mother, Like Daughter? Dietary and Non-Dietary Bone Fracture Risk Factors in Mothers and Their Daughters - Kamila SOBAS; Lidia WADOLOWSKA; MalgorzataAnna SLOWINSKA; Magdalena CZLAPKA-MATYASIK; Justyna WUENSTEL; Ewa NIEDZWIEDZKA (Iranian Journal of Public Health, 2015)
Background: The aim of this study was to demonstrate similarities and differences between mothers and daughters regarding dietary and non-dietary risk factors for bone fractures and osteoporosis.